Blastomycosis Presenting as Multiple Splenic Abscesses: Case Report and Review of the Literature - Sami Al-Nassar; Tracy MacNair; Jeremy Lipschitz; Howard Greenberg; Elly Trepman; Sate Hamza; John M Embil (Canadian Journal of Infectious Diseases and Medical Microbiology)
A 31-year-old Canadian Aboriginal man from northwestern Ontario presented with left upper quadrant pain and a tender left upper quadrant mass. Evaluation with a computed tomography scan showed multiple lesions within the spleen, a collection between the splenic tip and splenic flexure of the colon, and several small adrenal lesions. Computed tomographic-guided needle biopsy showed necrotizing granulomatous inflammation and multinucleated giant cells. Gomori’s methenamine silver stain showed broad-based budding yeast consistent with Blastomyces dermatitidis. Abdominal symptoms resolved after two months of oral itraconazole. Multiple splenic abscesses are a rare presentation of blastomycosis and should be considered in the differential diagnosis of left upper quadrant abdominal pain in a patient with a history of travel or residence in a region endemic for B dermatitidis.